2014
DOI: 10.1177/1758573214530607
|View full text |Cite
|
Sign up to set email alerts
|

Deltoid compartment syndrome as a complication of lateral decubitus positioning for contralateral elbow surgery in an anabolic steroid abuser

Abstract: Compartment syndrome as a result of patient positioning for surgery is a rare but serious complication. Compartment syndrome as a result of anabolic steroid use is more rare. We present a unique case of compartment syndrome related to anabolic steroid use and patient positioning for complex distal humerus fracture fixation and also provide a review of the literature related to this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Whilst in most anatomical areas fasciotomy of a compartment results in dissipation of the intracompartmental pressure, reports suggest that decompression by fasciotomy may not be as effective in DCS [2][3][4]. There is a paucity of evidence in the literature, but reports suggest that multiple incisions in the epimysium may be required to ensure adequate decompression [2,3,5]. Indeed, Rohde and Goitz described a case of DCS where the compartment pressures did not normalise until the epimysium was removed [3].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst in most anatomical areas fasciotomy of a compartment results in dissipation of the intracompartmental pressure, reports suggest that decompression by fasciotomy may not be as effective in DCS [2][3][4]. There is a paucity of evidence in the literature, but reports suggest that multiple incisions in the epimysium may be required to ensure adequate decompression [2,3,5]. Indeed, Rohde and Goitz described a case of DCS where the compartment pressures did not normalise until the epimysium was removed [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the prevention of deltoid compartment syndrome, a bean bag and large axillary roll can be used, although the case described by Rohde et al emerged despite these precautions. Wijesuriya et al suggest fastidious monitoring of patients who have used anabolic steroids with the possibility of transitioning to an alternative position such as prone if the surgical case is lengthy 15 .…”
Section: Rhabdomyolysis/compartment Syndromementioning
confidence: 99%
“…Rohde et al report one of the earliest cases of deltoid compartment syndrome after surgery in the LDP in a 35-year-old man with traumatic clavicular, scapular, and glenoid fractures 14 . Wijesuriya et al reported a case of deltoid compartment syndrome complicated by anabolic steroid use in a 20-year-old man who underwent fixation of the contralateral distal humerus 15 . Borenstein et al published a case report of a 36-year-old man who underwent surgery for an open fracture of the distal left humerus who developed contralateral right deltoid compartment syndrome 16 .…”
Section: Complicationsmentioning
confidence: 99%
“…Wijesuriya et al reported a case of a 20‐year‐old male patient who fell from a ladder and sustained an intra‐articular fracture of the right distal humerus and a stable undisplaced fracture of the right distal fibula. The patient was positioned in the left lateral position on a fracture table with pelvic support and the right arm was free over an L‐shaped bar without use of a tourniquet.…”
Section: How‐to Guidementioning
confidence: 99%